Identification of bester hybrids (female Huso huso Linnaeus, 1758 and male sterlet Acipenser ruthenus Linnaeus, 1758) using AFLP molecular technique - Yarmohammadi, M.; Shabani, A.; Pourkazemi, M.; Baradaran Noveiri, S. (2012)
In this study Amplified Fragment Length Polymorphism (AFLP) was applied to species identification of bester hybrids. Hybrids identification was performed by comparison of electrophoresis profiles with parental species. The simultaneous occurrence of diagnostic bands fixed in the parental species, genetic distance and identification and cluster analyses (UPGMA) allow a correct identification. We used 8 primer combinations (Eco+3, Mse+4) and a total of 250 bands (size range 40-1000 bp) were generated. Primer combinations of (E-AAT, M-CGAT) and (E-AAG, M-CGAT) produced diagnostic bands in hybrids and parental species. Moreover, the results of genetic identification showed that Bester hybrids are more similar to beluga (Huso huso) (0.68) in comparison with sterlet (Acipenser ruthenus) (0.45).The results suggested that this technique could be suitable for precise identification of species and inter-generic hybrids like bester.